THE PROBLEM OF FORMATION OF THINKING AND CREATIVITY IN TEENAGE STUDENTS - Nurmamatov Abdumalik Shermatovich (Western European Studies, 2025)
The article analyzes the problem of creativity with young adolescents. The author pays special attention to correctional and developmental work with young adolescents to develop their creativity, which requires a specially developed program based on the identified developmental features of boys and girls, content, form, and methods of psych correction
Keywords: younger adolescents; general and gender-specific characteristics of creativity; correctional and developmental program